2017
DOI: 10.12681/mms.2059
|View full text |Cite
|
Sign up to set email alerts
|

European anchovy (Engraulis encrasicolus) age structure and growth rate in two contrasted areas of the Mediterranean Sea: the paradox of faster growth in oligotrophic seas

Abstract: Copyright © 2017To cite this article: BASILONE, G., MANGANO, S., PULIZZI, M., FONTANA, I., GIACALONE, G., FERRERI, R., GARGANO, A., http://epublishing.ekt.gr | e-Publisher: EKT | Downloaded at 12/05/2018 11:19:51 | ARONICA, S., BARRA, M., GENOVESE, S., RUMOLO, P., MAZZOLA, S., & BONANNO, A. (2018). European anchovy (Engraulis encrasicolus) age structure and growth rate in two contrasted areas of the Mediterranean Sea: the paradox of faster growth in oligotrophic seas. Mediterranean Marine Science, 18(3) Intro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 51 publications
(70 reference statements)
0
20
0
Order By: Relevance
“…However, other studies pointed out that sardine juveniles prefer areas with moderate primary productivity values (Giannoulaki et al, 2011;Tugores et al, 2011) and negative relationships were also found between anchovy adults and primary productivity in other Mediterranean areas (Giannoulaki et al, 2008(Giannoulaki et al, , 2013Martín et al, 2008;Quattrocchi et al, 2016). Recent studies point out that primary productivity concentration is negatively correlated with anchovy individuals of age −1 (Bacha et al, 2010;Basilone et al, 2017). Overall, areas with high primary productivity concentration could affect water transparency, increasing the difficulty of finding prey (Fernández-Corredor, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, other studies pointed out that sardine juveniles prefer areas with moderate primary productivity values (Giannoulaki et al, 2011;Tugores et al, 2011) and negative relationships were also found between anchovy adults and primary productivity in other Mediterranean areas (Giannoulaki et al, 2008(Giannoulaki et al, , 2013Martín et al, 2008;Quattrocchi et al, 2016). Recent studies point out that primary productivity concentration is negatively correlated with anchovy individuals of age −1 (Bacha et al, 2010;Basilone et al, 2017). Overall, areas with high primary productivity concentration could affect water transparency, increasing the difficulty of finding prey (Fernández-Corredor, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This result is consistent with a comprehensive literature review (Fernández-Corredor, 2018). Temperature seems to affect the size of anchovy at the end of the first year of life, and was found positive related with anchovy at age-1 (Bacha et al, 2010;Basilone et al, 2017), and with anchovy body condition factors (Basilone et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In both these areas the habitat conditions are characterized by higher riverine input nutrients and higher productivity 25,31 than the oligotrophic waters of the study area and of the most part of the Mediterranean Sea 26 . The Strait of Sicily is considered an oligotrophic area 34,35,64 , where the enrichment of the upper water layers is associated with upwelling phenomena, which allow nutrient inputs from deeper waters 27,65 . Literature widely reported the variability in somatic growth linked to habitat variability e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Literature widely reported the variability in somatic growth linked to habitat variability e.g. 24,28,29,64,66,67 . The growth rate of the anchovy in the Strait of Sicily was at the low end of the range observed for this species among different areas, also including the Bay of Biscay and NW Mediterranean 24,31 .…”
Section: Discussionmentioning
confidence: 99%
“…Both the permanent and non-permanent character of the recognized physical features of the Central Mediterranean, as well as its degree of variability, have been studied (e.g., Olita et al, 2007;Gasparini et al, 2008;Drago et al, 2010;Placenti et al, 2013;Ben Ismail et al, 2014;Bonanno et al, 2014a;Jouini et al, 2016). Some studies singled out the influences of environmental variability on the biological resources in the Central Mediterranean (e.g., Levi et al, 2003;Garofalo et al, 2010;Rjeibi et al, 2010;Basilone et al, 2013Basilone et al, , 2015Basilone et al, , 2017Bonanno et al, 2013Bonanno et al, , 2014bBonanno et al, , 2015Fiorentino et al, 2013;Khoufi et al, 2014;Barra et al, 2015;Jaziri et al, 2015;Lauria et al, 2016;Gargano et al, 2017). However, only part of the main features affecting the ecosystems and living resources in the Central Mediterranean has been fully understood.…”
Section: Introductionmentioning
confidence: 99%